REVENUE ANALYSIS OF THE AGUNG CLASIC ALUMINUM HOUSEHOLD INDUSTRY IN PALU CITY - Sitti Rahma; Rita Suirlan, Sitti Rahmawati, Andi Herman Jaya, Failur Rahman (Adisam Publisher, 2024)
This research aims to analyze the income of glass and aluminum furniture in the Agung Class Aluminum home industry business in Palu City. This research uses qualitative research using primary and secondary data. Data collection was carried out through observation, interviews and questionnaires. The data analysis used is descriptive, namely calculating revenue, production costs and business income. The results of income analysis calculations show that the Agung Classic Aluminum household business is very profitable because the income received during one month is very large, namely IDR. 28,151,000,- per month, obtained from receipts of IDR. 62,100,000,- per month minus production costs of IDR. 33,948,704,-